2011
DOI: 10.4061/2011/107981
|View full text |Cite
|
Sign up to set email alerts
|

Breast Conservation Surgery: State of the Art

Abstract: Breast conservation surgery is available to the vast majority of women with breast cancer. The combination of neoadjuvant therapies and oncoplastic surgical techniques allows even large tumours to be managed with a breast-conserving approach. The relationship between breast size and the volume of tissue to be excised determines the need for volume displacement or replacement. Such an approach can also be used in the management of carefully selected cases of multifocal or multicentric breast cancer. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…This finding supports the approach to offer contralateral surgery in the primary setting only in selected cases, and otherwise as a secondary procedure after individual assessment. Since PRT can cause unpredictable changes to the breast [17, 18], it might be better to wait until the 1-year follow-up visit to see if contralateral surgery is needed. Achieving a better long-term symmetrical appearance when the “template,” in form of the cancer-treated breast, has reached its final outcome could be easier than trying to predict the change over time and compensate for this in the primary setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the approach to offer contralateral surgery in the primary setting only in selected cases, and otherwise as a secondary procedure after individual assessment. Since PRT can cause unpredictable changes to the breast [17, 18], it might be better to wait until the 1-year follow-up visit to see if contralateral surgery is needed. Achieving a better long-term symmetrical appearance when the “template,” in form of the cancer-treated breast, has reached its final outcome could be easier than trying to predict the change over time and compensate for this in the primary setting.…”
Section: Discussionmentioning
confidence: 99%
“…After operation with a volume displacement technique, a slight asymmetry can be expected regarding size and ptosis of the breast, although the shape of the breast and centralization of the nipple is preserved [13]. As symmetry is presented to be of great importance for patient satisfaction [14, 17, 21], many breast centers also operate on the contralateral breast in the primary setting to ensure postoperative symmetry. However, there are no firm guidelines specifying in which cases contralateral surgery should be performed, and a recent interview study showed that patients accept a slight asymmetry due to concerns regarding risks with surgery and the will to preserve the untouched contralateral, healthy breast [22].…”
Section: Introductionmentioning
confidence: 99%
“…Differently from volume displacement techniques, symmetrization of the contralateral breast is usually not required in cases of volume replacement techniques. 6 , 12 , 13 Standardized algorithms are not available, but many articles have been published in the attempt to provide a guide to help oncoplastic breast surgeons decide the best surgical procedure to apply to each single case. In a recent review, 9 the indication for either volume displacement or volume replacement techniques was essentially based on the expected percentage of breast volume excised: up to 10%, the result is considered satisfactory using simple wide local excisions, in cases between 10% and 20% of breast volume loss the use of volume displacement techniques should be favored, finally, for resections above 20% more complex approaches using tissue transfer and volume replacement are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 different approaches (volume displacement and volume replacement) are differently indicated depending on tumor size, location, and breast characteristics. 6 , 12 , 13 On the one hand, volume displacement applies different surgical techniques to reshape the breast and to correct the defect created during lumpectomy or quadrantectomy with dermo-glandular flaps of breast tissue; on the other hand, volume replacement procedures employ autologous reconstruction techniques like the use of local flaps where volume is missing. Volume replacement procedures have evolved over time from the use of the entire latissimus dorsi (LD) muscle to the use of pedicled perforator flaps available in the thoracic region such as the thoracodorsal artery perforator (TDAP) flap, the intercostal artery perforator flaps, the lateral thoracic artery perforator flap, and the serratus anterior artery perforator flap.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in the 1970s showed that radical mastectomy has no benefit over less aggressive surgeries in terms of either disease recurrence or overall survival [11,13]. Later, less aggressive breast conservation surgery became more common for local therapy combined with a wide variety of systemic adjuvant therapies [14]. Adjuvant therapies given systemically are aimed at eradicating disseminated cancer cells in order to minimize the probability of metastatic growth [15].…”
Section: Current Therapiesmentioning
confidence: 99%